Artificial intelligence revolutionizing type 2 diabetes mellitus self management (DSM): A digital breakthrough - Hadif, Mohammad; Fatima, Kashaf; NasrumminAllah, Maryam (Journal of the Pakistan Medical Association, 2025)
Dear Madam, Diabetes Mellitus (DM) is a chronic metabolic disorder characterised by persistently elevated plasma glucose levels and is one of the leading causes of global chronic health problems globally¹. International Diabetes Federation (IDF) reports that 537 million people live with DM, With projections of 643 million by 2030 and 783 million by 2045². Pakistan ranks among the top 10 countries with the highest Diabetes cases, with Type 2 Diabetes Mellitus (T2DM) caused by endogenous resistance of the body cells to insulin leading to chronic hyperglycaemia being a significant public health issue due to increased deaths, especially among the 40-60 age group¹. Given the sharp increase in cases, it is pertinent to understand the factors contributing to its increased incidence, such as genetics, dietary habits of complex protein intake, birth weight, sedentary lifestyle, lack of physical activity, high-calorie intake, cigarette smoking, and obesity¹. Thus, early identification is crucial for preventing disability and death in high-risk individuals. This involves patient education, screening, and ongoing medical care to prevent acute complications like ketoacidosis and reduce long-term risks which impact practically every organ in the body, including retinopathy, nephropathy, neuropathy, diabetic foot, stroke, and cardiovascular complications³. Diabetes management necessitates commitment to a variety of self-care practices that are frequently quite taxing for patients: meal planning, carb counting, exercise, blood glucose monitoring, and daily activity adjustment. Therefore, Diabetes self-Management (DSM) has always been challenging to both patients and Health care professionals. But over the past decade, the diabetes management paradigm has been significantly transformed by the integration of new technologies, with AI playing a crucial role in recognizing Diabetes Self-Management (DSM) apps as essential therapeutic aids for patients4. Diabetes management apps offer documentation and analysis of various parameters like blood glucose, eating habits, physical activity, and medical therapy4,5. These apps also track disease progression and facilitate communication between patients and caregivers4,5. Compared to patients in the control group, patients who got coaching and decision support via the Well Doc app showed higher reductions in haemoglobin A1c (HbA1c) levels5. The FareWell app was used in cohort research that found adults with type 2 diabetes to have the same effect, and those users reported feeling more confident about controlling their condition5. To prevent Diabetes Mellitus Type 2, a recent study by Esrat Jahan et al. Shows the potential advantages of smartphone applications by lowering obesity6. ---Continue